Eliciting features of 2D greenwater overtopping of a fixed box using modified dam break models. (March 2019) - Zhang, Xiantao; Draper, Scott; Wolgamot, Hugh; Zhao, Wenhua; Cheng, Liang
Abstract: Greenwater overtopping of a 2D fixed rectangular box due to focused wave groups is investigated using Computational Fluid Dynamics (CFD). Simulations span a wide parameter space, such that a range of overtopping types previously observed in experiments - including dam-break, plunging plus dam-break and hammer fist events - are observed. For each greenwater event the horizontal momentum flux and overtopping volume are computed, as these represent integrated quantities linked to damage potential on offshore facilities. These values are compared to simplified predictions based on the classical dam-break model with the dam height based on a run-up calculation on the box. It is found that these predictions deviate from measurements made in the CFD simulations because the classical model omits physics evident during overtopping events. Modifications to the classical dam-break model are presented to account for (i) the finite duration of an overtopping event; (ii) the finite quantity of water in the crest of a wave which exceeds the freeboard; (iii) the local geometry at the edge of the box; and (iv) the horizontal momentum in the crest of a wave which exceeds the freeboard. Insight gained from the first of these corrections leads to a new parameter- the relative overtopping duration T ', defined as the ratio of the duration for which fluid exceeds the freeboard to the natural time scale for runout of a dam with height equal to maximum run-up above freeboard. It is found that this new parameter dramatically reduces scatter in the integrated quantities. The results suggest that this new parameter, which combines freeboard exceedance and overtopping duration, may be an efficient indicator for screening metocean conditions to identify design sea states.